Gut Microbiota Diversity in 16 Stingless Bee Species (Hymenoptera: Apidae: Meliponini) - María de Lourdes Ramírez-Ahuja; Kenzy I. Peña-Carrillo; Mayra A. Gómez-Govea; Mariana Lizbeth Jiménez-Martínez; Gerardo de Jesús Trujillo-Rodríguez; Marisol Espinoza-Ruiz; Antonio Guzmán Velasco; Adriana E. Flores; José Ignacio González-Rojas; Diana Reséndez-Pérez; Iram Pablo Rodríguez-Sánchez (Microorganisms, 2025)
Bacterial symbionts play an important role in insect survival by contributing to key metabolic and defensive functions. While stingless bees are known to harbor diverse microbial communities, their core bacterial symbionts remain poorly characterized. In this study, we analyzed the gut microbiota of sixteen stingless bee species collected from different regions of Mexico using 16S rRNA gene sequencing on the Illumina® MiSeq™ platform. Our results revealed that Proteobacteria, Firmicutes, and Actinobacteria are the most abundant bacterial phyla across species. Among the dominant genera, lactic acid bacteria, such as Lactobacillus spp., Bifidobacterium, and Fructobacillus spp., were the most prevalent. These bacteria are responsible for developing biochemical functions in metabolic processes like lactic fermentation and the biotransformation of complex organic compounds into molecules that are more easily assimilated by bees. This study offers a novel perspective on the diversity and predicted composition of gut microbiota in Mexican stingless bees. By highlighting differences in microbial communities among species with different feeding habits, our results emphasize the importance of preserving microbial biodiversity in these pollinators.